Case Studies of Fiscal Councils : Functions and Impact. (Policy Papers; Policy Paper, 2013)
This supplement presents case studies of seven fiscal councils and examines how each council performs its core functions and if and how it impacts on the fiscal policy debate. The seven fiscal councils are: Belgium (Conseil Superieur des Finances-HCF), Canada (Parliamentary Budget Officer-PBO), Hungary (Koltsegvetesi Tanacs), Korea (National Assembly Budget Office-NABO), the Netherlands (Centraal Planbureau-CPB), Sweden (Finanspolitiska radet), and the United States (Congressional Budget Office-CBO). The main paper presents the comparative lessons and the general findings of this study based on a systematic comparison of these fiscal councils' experiences. This supplement discusses in detail each individual fiscal council's experiences.